PEMANFAATAN ABU VULKANIK GUNUNG KELUD SEBAGAI PENGGANTI SEBAGIAN AGREGAT HALUS PADA BETON NORMAL SEBAGAI PENDUKUNG BAHAN AJAR MATA KULIAH TEKNOLOGI BETON (PADA MAHASISWA PTB, JPTK, UNS) - Anshory, Abdul Rohman; Sumarni, Sri; Roemintoyo, Roemintoyo (Pendidikan Teknik Bangunan, 2015)
The purpose of this study was to determine (1) Effect of volcanic ash in partial replacement of the total fine aggregate of compressive strength and the density of the concrete, (2) resistance to the optimal compression of the concrete (3) optimum density concrete. (4) The teaching material obtained in the course of concrete technology on the effect of volcanic ash on the compressive strength of concrete and normal density.Experimental studies using methods and analytical techniques using a quantitative analysis of regression. Variables in the study were (1) the dependent variable: the strength of concrete in compression and the density of concrete, (2) independent variables: the variation of 0%, 10%, 15%, 20% and 25% Volcanic ash from the total weight of the sand. The sampel is  in the form of a cylinder with a diameter of 150 mm and a height of 300 mm.Based on the results of the study concluded that (1) changes in volcanic ash as a partial replacement of the fine aggregate strong overall influence on the compressive strength and density of concrete, (2) the optimal value of compressive strength and the weight of each type of concrete which is the variation of volcanic ash 8,36% amounted to 23,231 MPa, 11,889% to 22,919 MPa, (3) the value of the optimal concrete mixture as a whole, to namely the variation of volcanic ash 11,889% (4) in the form of teaching material to supplement teaching materials using Kelud volcanic ash as a partial replacement of fine aggregate on in terms of compressive strength concrete and density.Key words: normal concrete, volcanic ash, compressive strength, density.